New mutation identified in two sisters with adult‐onset erythropoietic protoporphyria. (20th April 2013) - Azad, J.; Brennan, P.; Carmichael, A. J.
Summary Background Erythropoietic protoporphyria (EPP; OMIM #177000) is a rare disease that usually presents in infancy or early childhood. The uncommon adult‐onset EPP is often associated with acquired somatic mutations of the FECH gene, secondary to blood dyscracias. Methods We investigated two sisters with adult‐onset EPP. Results We found a novel germline mutation in the FECH gene, in trans with the common hypomorphic IVS3‐48C allele. Conclusions The adult presentation and identical genotypes of the two sisters suggests that the late development of the condition is to an extent a function of the mutation. The exact mechanism for this delayed penetrance is not clear, although these atypical cases raise the possibility of other genetic or nongenetic disease‐modifying factors.